A new species of Anarta Ochsenheimer, 1816 from Mongolian and Russian Altai (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Ivanova, Maria S. (Zootaxa, 2014)
Anarta Ochsenheimer, 1816 is a hadenine genus restricted to Palaearctic and Nearctic Regions. The genus includes about 80 described species and subdivided into seven subgenera (Hacker 1998; Fibiger et al. 2011): Trichoclea Grote, 1883 (= Hadula Staudinger, 1889), Cardiestra Boursin, 1963, Ptochicestra Hacker, 1998, Aglossestra Hampson, 1905, Calocestra Beck, 1991, Pulchrohadula Hacker, 1998 and Anarta Ochsenheimer, 1816 (= Discestra Hampson, 1905). The group has been revised by Hacker (1998). Anarta, Trichoclea, Hadula and Discestra were been synonymized by Fibiger & Hacker (2005).